Viroterapi Sebagai Terapi Kanker - Mardiani, Dian; Djannatun, Titiek (Majalah Kesehatan Pharmamedika, 2013)
The development of molecular biology and genetic engineering, now allow the formation of an effective and specific cancer treatment. Modern cancer treatment has grown rapidly, thus giving a chance to discover a new method that is more promising than the previous treatment. Virotherapy is one of cancer therapy that use the replication-competent viruses to destroy cancer cells. Oncolytic virus (virus used as virotherapy) must be modified by genetic engineering before it can be used as virotherapy.Once modified, oncolytic virus destroys cancer cells through the replication, apoptosis induction, cell lysis through the release of progeny viruses, and activation of immune system. The immune system will be responsible for neutralizing the virus after tumour lysis process, and the immune system will also destroy the remaining tumor cells, although virus already neutralized from the body.